Implementation of endorphin massage for maternal care: A narrative literature review - Ni Luh Putu Sri Ariani; Ni Gusti Kompiang Sriasih; Gusti Ayu Tirtawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Endorphin massage is one of the non-pharmacological interventions in maternal care used to help reduce mothers’ physical and psychological discomfort during pregnancy, labor, and postpartum. Purpose: To Implementation of endorphin massage for maternal care. Method: This study used a narrative literature review method with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Literature searching was conducted through Google Scholar, PubMed, and ScienceDirect databases using the keywords “endorphin massage”, “maternal care”, “labor pain”, “postpartum”, and “non-pharmacological therapy”. The articles included quantitative studies published in Indonesian and English from 2020–2025. Based on the selection process, 10 articles met the inclusion criteria. Results: The review showed that endorphin massage was effective in reducing labor pain, decreasing anxiety, improving maternal comfort, supporting breast milk production, and facilitating the labor process. In addition, this therapy was considered safe, easy to apply, cost-effective, and had minimal side effects. Conclusion: Therefore, endorphin massage has the potential to become a complementary intervention in holistic and mother-centered midwifery care (woman-centered care).